Analisis Self-Esteem Anak Berkebutuhan Khusus di SMA Negeri 3 Padang serta Implikasinya dalam Bimbingan dan Konseling - Ngadiman, Dyah Ayu Sakinah; Yendi, Frischa Meivilona; Nurfarhanah, Nurfarhanah; Putriani, Lisa (Universitas Negeri Padang, 2023)
Children with special needs are children who need the same education and services as other children, so that they can realize that every human being must have advantages. One of the problems of children with special needs is their low self-esteem. Therefore, the problem to be studied in this research is,